Rituals of Passage: The Dayak Bakumpai Funeral Ceremony and its Religious Significance in Muara Tuhup Village, Central Kalimantan - Wijaya, Ahmad Razikin; Rahmadi, Rahmadi; Saputra, Riza; Agustina, Dewi (IAIN Palangka Raya, 2024)
The research is motivated by the phenomenon of funeral ceremonies in the Muara Tuhup Village. The research aimed to analyze The Dayak Bakumpai Funeral Ceremony and its Religious Significance in Muara Tuhup Village, Central Kalimantan. The research used a qualitative approach, with the research subject being the Dayak Bakumpai community involved in funeral ceremonies. Data were collected through participatory observation, interviews, and documentation. Data was analyzed using reduction, display, and data verification. The study results show that the Dayak Bakumpai funeral ceremony in Muara Tuhup combines local traditions with Islamic values in harmony. Also, it has a